2019
DOI: 10.1111/tmi.13238
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of non‐specialist versus specialist health workers in diagnosing hearing loss and ear disease in Malawi

Abstract: Objective To determine whether a non‐specialist health worker can accurately undertake audiometry and otoscopy, the essential clinical examinations in a survey of hearing loss, instead of a highly skilled specialist (i.e. ENT or audiologist). Methods A clinic‐based diagnostic accuracy study was conducted in Malawi. Consecutively sampled participants ≥ 18 years had their hearing tested using a validated tablet‐based audiometer (hearTest) by an audiologist (gold standard), an audiology officer, a nurse and a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 28 publications
2
40
1
Order By: Relevance
“…Pure tone audiometry can now be conducted using validated smartphone-based tests which are automated [27]. The advantages of smartphone-based tests over screening audiometers in survey settings is portability, and ability for non-specialist staff to undertake the tests [28]. Therefore, the presence of audiologists in the field may not be required, although this needs further verification.…”
Section: Discussionmentioning
confidence: 99%
“…Pure tone audiometry can now be conducted using validated smartphone-based tests which are automated [27]. The advantages of smartphone-based tests over screening audiometers in survey settings is portability, and ability for non-specialist staff to undertake the tests [28]. Therefore, the presence of audiologists in the field may not be required, although this needs further verification.…”
Section: Discussionmentioning
confidence: 99%
“…Then, a pilot study of the survey protocol was undertaken in Malawi to determine the appropriate cluster size, and whether the data collection protocol needed adaptations. Finally, a clinic-based diagnostic accuracy study was undertaken in Malawi to determine whether non-specialist health workers, instead of highly skilled professionals, could undertake the hearing test and ear examination [27]. The next section gives an overview of the developed methodology.…”
Section: Development Of Rahl Methodologymentioning
confidence: 99%
“…at least 30 people), two testers were required. The diagnostic accuracy study in Malawi found that non-specialist health workers can be trained to accurately assess hearing [27]. One ear examiner: to complete an ear examination using otoscopy and assign causes (Ear Nose and Throat (ENT) specialist).…”
Section: Data Collection Teamsmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2013-2014, all-age population-based surveys of disability were undertaken in one district each in India (Mahbubnagar District) and Cameroon (Fundong Health District). [15,16] These surveys measured VI and HI using both self-reported and clinical tools. Sample size calculations resulted in a target sample size of 4056 participants of all-ages in 51 clusters of 80 people.…”
Section: Rationale For Combining Raab and Rahlmentioning
confidence: 99%